Increase ofthe productivity of a greenhouse tomato crop improving the pollination (2001)
The lack ofpollination practices is limiting the actual yields of the greenhouse tomato crops in Colombia. In order to evaluate the effect of pollination on productivity and yield of tomatoes in the Bogotá Plateau and its importance on quality and fruit development rate, two practices of pollination were evaluated: the use of an electrical vibrator or "mechanical be e" and the vibration of the plants by means of striking the guiding wires. The results indicate that the use ofthe electrical vibrator increases the production in 34 % per plant. Fresh weight, fruit diameter and number of seeds per fruit (163,3 g, 70 mm and 128 seeds per fruit respectively) incremented with this practice. The fruit growth period of electrical vibrated fruits was shorter (63,9 days) than the control treatment. For all the measured variables, the wire striking treatment did not show significant increments. A marginal analysis of cost and benefits showed that the use of the electrical vibrator is a profitable practice, not only because it increases fruit production, but also because a higher proportion of big fruitswith greater market value is obtained.